(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the trend of mortality from ischemic heart (IHD) and cerebrovascular diseases (CVD) in Brazil and regions from 1980 to 2018. This is an ecological study, which evaluated data on mortality from IHD and CVD in Brazil and regions, from 1980 to 2018. Data from 1980 to 1996 came from CID-9 and from 1997 to 2018 from CID-10. The crude mortality rate (MR) and the standardized mortality rate (SMR) were calculated. For trend analysis, simple linear regression was chosen. Excel 2019 and BioEstat 5.0 were used. In Brazil, the average of SMR was 68 cases per 100,000 inhabitants for the IHD group in the entire time series. There is a 45.43% decrease in mortality from 1980 to 2018 across the country. In the analysis of the trend of mortality due to IHD, only the Northeast and the North showed an upward trend in cases (p<0.05). Regarding CVD, the national average of SMR was 74.5/100 thousand with emphasis on the south with 91.7/100 thousand. In the time series, Brazil showed a reduction of 60.2% in cases, with 104.7 cases/100 thousand in 1980 and 41.6/100 thousand in 2018. Only the Northeast and the North showed a trend towards an increase in cases (p <0.05). This study contributes with information that allows for better control, prevention and monitoring of cardiovascular diseases, as interventions are concentrated in each region of the country, aiming to reduce inequalities in public health.